2016
DOI: 10.1038/srep29666
|View full text |Cite
|
Sign up to set email alerts
|

The Dentin Sialoprotein (DSP) Domain Regulates Dental Mesenchymal Cell Differentiation through a Novel Surface Receptor

Abstract: Dentin sialophosphoprotein (DSPP) is a dentin extracellular matrix protein that is processed into dentin sialoprotein (DSP), dentin glycoprotein (DGP) and dentin phosphoprotein (DPP). DSP is mainly expressed in odontoblasts. We hypothesized that DSP interacts with cell surface receptors and subsequently activates intracellular signaling. Using DSP as bait for screening a protein library, we demonstrate that DSP acts as a ligand and binds to integrin β6. The 36 amino acid residues of DSP are sufficient to bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Our study demonstrated that ICF induced a more than 100-fold increase in ITGB6 mRNA expression compared with the unloaded condition, implying the potential participation of ICF in controlling hPDL behavior. In a mouse dental papilla mesenchymal cell line, integrin β6 bound to dentin sialoprotein and subsequently induced cell attachment, migration, and Dmp1 and Dspp mRNA expression 50 , suggesting that integrin β6 is involved in the regulation of dental mesenchymal cell behavior. TGF-β1 positively regulated ITGB6 expression in oral cancer cells and gingival keratinocytes that may participate in cancer invasion and periodontal inflammation, respectively 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that ICF induced a more than 100-fold increase in ITGB6 mRNA expression compared with the unloaded condition, implying the potential participation of ICF in controlling hPDL behavior. In a mouse dental papilla mesenchymal cell line, integrin β6 bound to dentin sialoprotein and subsequently induced cell attachment, migration, and Dmp1 and Dspp mRNA expression 50 , suggesting that integrin β6 is involved in the regulation of dental mesenchymal cell behavior. TGF-β1 positively regulated ITGB6 expression in oral cancer cells and gingival keratinocytes that may participate in cancer invasion and periodontal inflammation, respectively 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent study shows that BMP‐2 activates Dspp transcription and that is mediated by OSX in vitro . Additionally, Smad1/5/9 directly binds to SBEs in the Dspp promoter from −211 to −183 bp and activates Dspp transcription . These findings suggest that canonical BMP‐Smad signaling pathway plays a key role in regulating Osx and Dspp transcription.…”
Section: Discussionmentioning
confidence: 90%
“…(30) Additionally, Smad1/5/9 directly binds to SBEs in the Dspp promoter from −211 to −183 bp and activates Dspp transcription. (37) These findings suggest that canonical BMP-Smad signaling pathway plays a key role in regulating Osx and Dspp transcription. Here, we showed that the loss of BMP signaling in odontoblasts decreased Osx and Dspp expression, suggesting that BMP signaling via BmpR1A regulates Osx and Dspp expression to promote dentin formation and mineralization.…”
Section: Discussionmentioning
confidence: 92%
“…This feature could be explained by the observation that dentin and bone are similar in chemical composition and structural organization, both showing collagen and mineral crystal deposition at the micro-and nanometer levels. Moreover, dentin has an absolute number of NCPs, including dentin sialoprotein, osteopontin, dentin matrix protein-1, and matrix extracellular phosphoglycoprotein, 18,19 which are thought to influence cell behavior. 39 For example, osteocytic proteins, which are expressed in bone but not in dentin, may suppress osteoclast formation during the bone remodeling process.…”
Section: Osteoclast Activation With Rhbmp-2mentioning
confidence: 99%
“…[14][15][16][17] As a major component of teeth, dentin is an acid-insoluble, acellular, avascularized type I collagenous scaffold with nanoporous dentinal tubules containing minerals and noncollagenous proteins (NCPs), including GFs. 18,19 Among the many human dentin matrix-derived GFs (HD-GFs), endogenous dentin BMPs (ED-BMPs), which are similar to bone matrix-derived BMPs, have been identified and purified, showing similar actions in vivo. 20 The dentin matrix comprises four types of calcium phosphate (e.g., hydroxyapatite, b-tricalcium phosphate, amorphous calcium phosphate, and octacalcium phosphate) with low crystalline apatite, which possess higher solubility.…”
Section: Introductionmentioning
confidence: 99%